Given that g(3)=-3 and h(5) = 3 what is f(5) if f(x) = g( h(x) ).

2 Answers

rubeus-hagrid's profile pic

rubeus-hagrid | (Level 1) Adjunct Educator

Posted on

f(5)=g(h(5))

h(5)=3

f(5)=g(3)

g(3)=-3

f(5)=-3

justaguide's profile pic

justaguide | College Teacher | (Level 2) Distinguished Educator

Posted on

It is given that g(3)=-3 and h(5) = 3. We are required to find f(5) if f(x) = g(h(x))

f(x) = g(h(x))

f(5) = g(h(5))

but h(5) = 3

=> f(5) = g(3)\

but g(3) = -3

=> f(5) = -3

The required value of f(5) = -3